Detecção por PCR em tempo real e identificação molecular de clostridium estertheticum proveniente de carne bovina e ambientes de matadouros frigoríficos brasileiros - Marra, Kelly Nobre (2012)
The involvement of Clostridium estertheticum as agents of deterioration of chilled beef packaged under vacuum from slaughterhouse brazilian, has been reported since 2007. Once detected, and presents the main sources of contamination in slaughter establishments, there was the need to advance the search for new knowledge about this Clostridia, however, the classical microbiological methods for their detection are considered difficult to implement because they require hard work and take a long time. PCR can be a quick and efficient detection of clostridia incriminated in the deterioration of beef chilled vacuum packaged and refrigerated environments slaughterhouses, without isolation of pure cultures. The objective of this study was to develop a test for realtime PCR for detection of Clostridium estertheticum in bovine meat and environments of slaughterhouse brazilian, as well as the molecular identification of isolates of Clostridium estertheticum by means of AFLP and RFLP techniques - PCR. The analytical results were compared with conventional PCR and confirmed by isolation. The Real-Time PCR assay for detection of Clostridium estertheticum in bovine meat and environments of slaughterhouse brazilian, was efficient. Evidence for the presence and distribution of C. estertheticum the sources studied and the technique of RT-PCR provided the highest percentage of positive samples from slaughterhouses that refrigerators Conventional PCR, and this is confirmed by isolation, which has become an important alternative for the detection of C. estertheticum in bovine meat and environments of slaughterhouse without isolation. The isolates used showed general similarity of 42.4%, suggesting high genetic diversity. In addition, the isolates obtained from samples of ambient and refrigerated meat tufted not show significant similarity, greater than 80%, used with any typical strain. The similarity found between the isolates may be indicative of possible similarity between those from meats and puffed from between those environments and equipment. The study revealed that additional steps necessary x for the characterization of Brazilian isolates, especially sequencing of other regions of the DNA so as to determine their taxonomic position.